DECARBONIZATION AND ECOMODERNIZATION OF THE ECONOMY AS A RESOURCE-ENERGY-EFFICIENT WAY OF POST-WAR RECONSTRUCTION OF UKRAINE - Vasyl Petruk; Andriy Polyvyanchuk; Galina Petruk; Kostyantyn Hura; Volodymyr Faichuk (Environmental Problems)
Global climate changes are taking place on our planet, which cause an increase in the average annual tempe-rature of the atmospheric air, and, therefore, rapid melting of glaciers on all continents and an inevitable rise in the level of the world ocean. This, in turn, can lead to “environmental” wars, a brutal struggle for survival resources, and powerful migration processes. At the same time, one of the main reasons for such global changes and processes is the huge amount of emissions of greenhouse gases and soot particles into the surface layer of the atmosphere (troposphere), caused by anthro-pogenic and man-made activities, outdated energy-intensive technologies that involve the excessive extraction and use of carbon-containing raw materials, their burning and emission into the atmosphere. However, an alternative to this in post-war Ukraine can only be decarbonization and eco-moderniza-tion of its economy based, first of all, on renewable energy sources (in particular, the inexhaustible energy of the Sun), resource-saving, closed, recycling, emission-free and other mo-dern innovative environmental protection and energy-efficient technologies. That is, humanity must definitely go on the path of “green” transformation of not only the economy, but also the greening of all other spheres of life (Hura, Petruk, 2021).